Prevalence of metabolic syndrome and its determinants in older Mexican non-diabetic adults - Aleman-Mateo, Heliodoro (Grupo Aran, 2018)
Introduction: the prevalence of metabolic syndrome (MetS) is high in older people, and several factors have been explored as main determinants.However, few data exist for older people from low- and middle-income countries. Therefore, our objective was to estimate the prevalence of MetS. Secondly, to explore which of the cardio-metabolic, body composition, inflammatory and demographic risk factors were associated with the prevalence of MetS in a population of older Mexican adults. Methods: data for this analysis were collected in subjects over 60 years of age from northwest Mexico. Fasting and two-hour glucose, fasting insulin, homeostasis model assessment of insulin resistance, lipid profiles, markers of adiposity and inflammation, and blood pressure were assessed. In addition, anthropometry and body composition data, levels of physical activity and demographic variables were also considered. MetS was diagnosed by three different criteria. Results: total sample size was 369 subjects. The prevalence of MetS varied widely, from 36% to 52% depending on the criteria applied, but regardless of the criteria, all subjects with MetS were heavier and more overweight, and had higher triglyceride values and lower values of total HDL-cholesterol compared to those without MetS (p < 0.0001). Final models adjusted for age showed that, regardless of the diagnostic criteria applied, fat mass, the homeostasis model assessment and some demographic variables were main determinants of MetS in this sample of older people without diabetes. Conclusions: the prevalence of MetS is relatively high in non-diabetic older adults and it was associated with some biological and demographic factors as the main determinats.